PENGARUH PARALEL PENTANAHAN TRANSFORMATOR DAN PENTANAHAN ARRESTER TERHADAP KINERJA RESISTANSI PENTANAHAN TRANSFORMATOR DISTRIBUSI 250 KVA GARDU BA 005 di PT. PLN (PERSERO) UP3 BENGKULU ULP TELUK SEGARA (Jurnal Ampere, 2020)
The grounding system in the distribution transformer substation is very important for the reliability of the supply of electrical energy and protects humans and equipment from overvoltages or leakage currents, besides that the mainly good neutral grounding system will produce the perfect voltage. To protect humans and distribution substation equipment BA 003 Distribution Transformer 250 KVA from touch voltage, especially in the dry season, sunny weather and peak loads using a 250 KVA Transformer requires parallel grounding Arrester and Grounding Body or Transformer shell. From the measurement results, the peak load occurs at night with the loading reaching 54% of the 250 KVA distribution transformer capacity of 194 KVA. For the measurement of the largest resistance on the grounding of the Transformer Arrester of 8.1 Ω, occurs at 14.00 - 15.00 WIB, the greatest resistance on the grounding of the Transformer Body or Shell of 8.3 Ω occurs at 14.00 - 15.00 WIB. From the parallel measurement of the grounding installation of the Transformer Arrester and the Transformer Body or Shell of 7.7 Ω at 14.00 - 15.00 WIB, with sunny weather conditions during the day.ABSTRAK Sistem Pentanahan  pada gardu transformator distrbusi sangatlah penting untuk kehandalan suplai energi listrik serta melindungi manusia dan peralatan dari tegangan lebih atau arus bocor, selain itu sistem pentanhan terutaman pentanhan netral yang baik akan menghasilkan  tegangan yang sempurna. Untuk melindungi manusia serta perangakat gardu distribusi BA 003 Transformator Distribusi 250 KVA dari tegangan sentuh terutama pada musim kemarau, cuaca cerah dan  beban puncak penggunaan Transformator 250 KVA diperlukan paralel grounding Arrester dan Grounding Bodi atau cangkang Transformator. Dari hasil pengukuran  Beban puncak terjadi pada malam hari dengan pembebanan mencapai 54% dari kapasitas transformator distribusi 250 KVA sebesar 194 KVA. Untuk pengukuran Resistansi terbesar  pada pentanahan Arrester Transformator sebesar 8,1 Ω tejadi pada pukul 14.00 – 15.00 Wib, Resistansi terbesar pada pentanahan Bodi atau Cangkang Transformator sebesar 8,3 Ω terjadi pada pukul 14.00 – 15.00 Wib. Dari pengukuran  Paralel Instalasi pentanahan Arrester Transformator dan  Bodi atau Cangkang Transformator sebesar  7,7 Ω pada pukul 14.00 – 15.00 Wib, dengan kondisi cuaca pada siang hari Cerah